REASONING OF QUALITATIVE COMPOSITION OF MODERN WOUND-HEALING AGENTS BASED ON DECAMETOXIN AND METHYLURACIL FOR THE NEEDS OF THE MEDICAL SERVICE OF THE ARMED FORCES OF THE UKRAINE - Соломенний, Андрій (Modern engineering and innovative technologies, 2023)
The author has substantiated the concentration of methyluracil (in vivo) and decamethoxine (in vitro) for the development of the composition, technology, and biopharmaceutical research of an antimicrobial and wound-healing ointment with methyluracil, deca